The mystery illness - Lakin, Patricia 1944-; Cushman, Doug. (Austin, Tex. Raintree Steck-Vaughn, 1995)
Miss Yoo, the school nurse, deals with everything from chicken pox to a severe allergic reaction.
"The school nurse."
Keywords: Nurses -- Fiction; Schools -- Fiction